Інформаційна технологія аналізу фінансових даних на основі інтегрованого методу - Kuznyetsova, N. V.; Bidyuk, P. I. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2017)
In the paper the basic features of financial data are discussed and a new integrated method for financial data analysis is proposed. The new informational technology on the basis of integrated method of data analysis is proposed and its possibility of application for the borrower’s creditworthiness assessment is illustrated in practice.